Laboratory scale UV–visible degradation of acetamiprid in aqueous marketed mixtures - Structural elucidation of photoproducts and toxicological consequences. (June 2020) - Nicol, Edith; Varga, Zsuzsanna; Vujovic, Svetlana; Bouchonnet, Stéphane
Abstract: Acetamiprid is a neonicotinoid pesticide, which is extensively used on agricultural crops, but has a high toxic effect on beneficial insects and the human body. It is exposed to sunlight irradiation on crops but also in surface waters where it is found at a high level due to its resistance to common water treatments. The aim of the present work was to study the UV–visible photodegradation of acetamiprid, alone and in two marketed mixtures (Polysect Ultra SL® and Roseclear Ultra®). Ten photoproducts were characterized using LC-HR-MS/MS analysis. Photodegradation pathways were proposed based on the chemical structures of photoproducts and kinetic measurements; a matrix effect has been evidenced for commercial mixtures. Most photoproducts exhibit potential developmental toxicity twice higher than that of the parent compound. Regarding potential mutagenicity, all photoproducts are less toxic than acetamiprid. Estimated oral rat LD50 values show that the potential toxicities of photoproducts are similar or lower than that of acetamiprid. In vitro tests on Vibrio fischeri bacteria showed that the ecotoxicities of marketed mixtures are significantly higher than that of acetamiprid in aqueous solution; they slightly increase after UV-light exposure. Highlights: UV photodegradation of acetamiprid was investigated, alone and in marketed mixtures. Ten photoproducts were characterized using LC-HR-MS/MS analysis. Degradation pathways have been proposed based on photoproducts' structures. In vitro tests showed that marketed mixtures are more toxic after UV-light exposure.